1999
DOI: 10.1046/j.1360-0443.1999.941014996.x
|View full text |Cite
|
Sign up to set email alerts
|

Brief intervention for alcohol use in pregnancy: a randomized trial

Abstract: After a comprehensive assessment of alcohol use, subjects in both the AO and BI groups reduced their antepartum alcohol consumption. The importance of screening for prenatal alcohol use is underscored by the findings that any prenatal alcohol consumption increases the risk of continued antepartum drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
123
1
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(138 citation statements)
references
References 27 publications
5
123
1
9
Order By: Relevance
“…It has been noted that alcohol use, particularly in pregnancy, remains a socially stigmatised activity, and surveys of drinking behaviour in pregnancy may underestimate the true extent of alcohol consumption 130 through fear of social disapproval. 131 A Swedish study found that older age, living in a major city with low social support and using tobacco during pregnancy, as well as pre-pregnancy drinking, were predictors of women's drinking in pregnancy. 132 It has been suggested that increased awareness of the dangers of drinking in pregnancy has resulted in changes in women's behaviour, 133 but this may simply be a case of women reporting less alcohol consumption.…”
Section: Prevalence Of Alcohol Consumption In Pregnancymentioning
confidence: 99%
“…It has been noted that alcohol use, particularly in pregnancy, remains a socially stigmatised activity, and surveys of drinking behaviour in pregnancy may underestimate the true extent of alcohol consumption 130 through fear of social disapproval. 131 A Swedish study found that older age, living in a major city with low social support and using tobacco during pregnancy, as well as pre-pregnancy drinking, were predictors of women's drinking in pregnancy. 132 It has been suggested that increased awareness of the dangers of drinking in pregnancy has resulted in changes in women's behaviour, 133 but this may simply be a case of women reporting less alcohol consumption.…”
Section: Prevalence Of Alcohol Consumption In Pregnancymentioning
confidence: 99%
“…48 Physician advice or written educational information improves patients' knowledge of the risks of drinking during pregnan-cy. [55][56][57] Providing information alone may reduce the risk of an alcohol-exposed pregnancy through reduced consumption or increased use of effective contraception. Information's beneficial effects on reducing risk may persist for up to 9 months.…”
Section: Brief Intervention Among Pregnant Womenmentioning
confidence: 99%
“…Women who had been drinking in the previous 6 months, but not in the 90 days before the intervention, were also more successful in reducing alcohol consumption. 38,62 A detailed assessment, alone, was found to be as effective as an assessment followed by brief intervention in reducing alcohol consumption during pregnancy. However, brief intervention was more effective with the subgroup of heavier drinkers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Par contre, les femmes abstinentes au moment de l'inclusion le demeuraient plus souvent si elles bénéficiaient d'une intervention. Ces données suggèrent l'intérêt d'un programme de prévention portant sur la consommation d'alcool, même chez des femmes qui n'en consomment pas [10].…”
Section: Comment S'y Prendre?unclassified